Peran halal-friendly destination attributes dan experience dalam meningkatkan revisit intention dunia fantasi - Rafli, Muhammad; Balqiah, Ezni (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: One of the elements that is of concern to tourists and managers of tourist attractions is the factor of halal-friendly destination attributes which consist of aspects of social environment, halal-friendly facilities, halal-friendly services, halal food and beverages, and halal-friendly locals and staff. Findings: These five variables are the aspects most recognized by tourists to see whether the tourist object can be said to be halal or not. With the research object of Dunia Fantasi, the purpose of this research is to analyze the relationship between halal-friendly destination attributes variable and experience (4Es) assisted by perceived value and satisfaction to revisit intention of DKI Jakarta Muslim tourists towards Dunia Fantasi. Methods: There are 14 hypotheses that will be tested in this study and use a descriptive and quantitative research design. Data collection was carried out by distributing questionnaires cross-sectionally and using a non-probability sampling technique to 332 respondents. Structural Equation Modeling (SEM) with Covariance Based (CB) type is used as a method to test the available hypotheses using SPSS and Lisrel 8.80 software. Conclusion: The results of the study show that halal-friendly destination attributes and experience (4Es) have a partial effect on perceived value, satisfaction, and revisit intention.